2015
DOI: 10.7785/tcrt.2012.500391
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Three-dimensional Set-up Errors using Megavoltage Computed Tomography (MVCT) during Image-guided Intensity-modulated Radiation Therapy (IMRT) for Craniospinal Irradiation (CSI) on Helical Tomotherapy (HT)

Abstract: The purpose of this study was to assess three-dimensional (3D) set-up errors using megavoltage computed tomography (MVCT) during image-guided intensity-modulated radiation therapy (IMRT) for supine craniospinal irradiation (CSI) on helical tomotherapy (HT).Patients were immobilized in a customized 4-clamp thermoplastic head mask with or without whole-body vacuum cradle. Set-up was based primarily on a set of cranial fiducial markers. MVCT scans were acquired and co-registered with planning scan separately at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Their maximum mean deviation, in any direction, was found to be 6 mm while ours was 24 mm. Our results were, however, comparable to other similar studies investigating errors, uncertainties and margins for craniospinal treatments [34][35][36]. Stoiber et al [34] found a maximum deviation of 18 mm and 10°, again compared to our 24 mm and 9.6°.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Their maximum mean deviation, in any direction, was found to be 6 mm while ours was 24 mm. Our results were, however, comparable to other similar studies investigating errors, uncertainties and margins for craniospinal treatments [34][35][36]. Stoiber et al [34] found a maximum deviation of 18 mm and 10°, again compared to our 24 mm and 9.6°.…”
Section: Discussionsupporting
confidence: 91%
“…Stoiber et al [34] found a maximum deviation of 18 mm and 10°, again compared to our 24 mm and 9.6°. Gupta et al [35] found a maximum deviation of 20 mm. Interestingly, Thondykandy et al [36] found the SU to be larger than the RU for CSI while our results show the opposite.…”
Section: Discussionmentioning
confidence: 95%
“…The alignment of the patient was done rectilinearly on the couch. [ 13 ] Figure 1 shows the immobilization devices used at our institution.…”
Section: Methodsmentioning
confidence: 99%
“…For CSI, the imaging was carried out daily, and the correction was applied, based on the hospital protocol. [ 13 ]…”
Section: Methodsmentioning
confidence: 99%
“…range of MVCT compared to the long range of the treatment field in the craniocaudal direction required for CSI using HT (HT-CSI) 16,27,28 . Among these drawbacks, in terms of the image quality, Forrest et al and Meeks et al reported that MVCT can provide sufficient image quality for tumor identification and setup verification, despite its low-contrast resolution for soft tissues 29,30 .…”
mentioning
confidence: 99%